(untitled) (African Journal of Law and Politics, 2025)
This article discusses the applicability of sanctions on corporate bodies under OHADA law in Cameroon. Corporate entities are fictional or artificial entities created by the law, it is on this basis that we seek to address the problem of sanctioning corporation in a bijural system like the case of Cameroon. The Cameroonian law makers have put in place legislations with regards to sanctions that are imposed on corporate entities with some differences at the level of interpretation and applicability due to the bijural system applicable in the country. The doctrinal method has been employed which include primary and secondary sources of data, primary source of data consist of laws and legislations made in the country while secondary data consist of books, journals and legal writings with regards to Company Law in Cameroon. It is on this basis that this article analyses how corporate sanctions are imposed within the bijural legal system of Cameroon. The approaches employed by these two legal systems in the applicability of the laws are not actually accepted by those in the Common Law jurisdiction for lack of precisions in the law by those concerned. As to the realities of the day-to-day occurring in Cameroon, it is proposed that the Cameroonian legislators should enact precedes laws in sanctioning corporate bodies and also to harmonize its own laws with regard to corporate laws so as to meet with the aspirations of the present reality.